Doing poorly on purpose : strategies to reverse underachievement and respect student dignity - Delisle, James R., 1953- (ASCD ; Free Spirit Publishing, 2018)
By focusing on smart kids who get poor grades, veteran educator James R. Delisle dispels the negative associations and stereotypes connected to underachievement.